Public Expenditure Handbook : A Guide to Public Policy Issues in Developing Countries. (International Monetary Fund, 1991)
This handbook, edited by Ke-young Chu and Richard Hemming, offers guidance to officials formulating public policy recommendations, so that the aggregate level of public spending conforms with the economy's overall resource capacity. The handbook looks at the impact of public spending on the efficiency of resource use and explores the basis for distinguishing between productive and unproductive spending.